Developmental guidelines for good chairside teaching – a consensus report from two conferences. (12th November 2014) - Wilson, J.; Sweet, J.; Pugsley, L.
Abstract Developmental Guidelines for Chairside Teaching are a direct outcome of 10 years of research, originally prompted by feedback from undergraduate dental students who not only thought that the teaching they received was uneven and variable in quality, but also felt strongly that they learned more with educationally trained teachers than those with little or no teacher training. Workshops embracing the views of teaching colleagues from many other Dental Schools produced a consensus view that developmental guidelines for teachers would provide a valuable resource. A conference to consider all aspects on chairside teaching and learning was convened with delegates invited from all UK Dental Schools. This was subsequently followed by a second conference to develop specific guidelines for chairside teaching and learning. The Nominal Group Technique was used in the first chairside teaching conference, and Structured Small Expert Groups were used in the second. The overall consensus from these workshops and conferences were as follows: (i) developmental guidelines for chairside teaching can act as a useful resource for teachers to improve and maintain their standard of chairside teaching, (ii) developmental guidelines can be divided into themes of organisational issues and learner and teacher qualities, and (iii) Guidelines should be 'developmental' because they encourage chairside teachers to focus on the next immediate goal to maintain and improve quality and standards. These developmental guidelines could provide a universal toolkit for improved chairside teaching which would result in a better student learning experience. Set out in this way these guidelines have currency across academic and practical skills levels, different educational systems, philosophies and country boundaries.